2023 macroprudential stress test of the euro area banking system. Bank resilience in a changing environment: challenges and opportunities - Giuseppe Cappelletti; Ivan Dimitrov; Catherine Le Grand; Laurynas Naruševičius; André Nunes; Jure Podlogar; Nicola Röhm; Lucas Ter Steege (European Central Bank (ECB), 2024)
This paper presents the updated macroprudential stress test for the euro area banking system, comprising around 100 of the largest euro area credit institutions across 19 countries. The approach involves modelling banks' reactions to changing economic conditions. It also examines the effects of adverse scenarios as defined for the European Banking Authority's 2023 stress test on economies and the financial system as a whole by acknowledging a broad set of interactions and interdependencies between banks, other market participants and the real economy. Our results highlight the resilience of the euro area banking system and the important role banks' adjustments play in the propagation of shocks to the financial sector and real economy.
Keywords: C30; C53; C54; E52; 330; economic models; monetary policy; forecasting; macroeconometrics